Cutaneous myiasis due to Cochliomyia hominivorax in a drug user - Trombetta, Luis (2009)
Myiasis is the condition resulting from the invasion of tissues or organs of man or animals by dipterous larvae. The blowflies (Calliphoridae) of Argentina comprise several species that may cause myiasis by colonizing wounds or infected body orifices, and one specific parasite: Cochliomyia hominivorax. This species often causes traumatic myiasis in cattle, dogs and cats, and it is not rare in humans. The larvae consume living tissues, so they are dangerous unless speedily removed. Immediate operative exploration along with the removal of larvae and primary defect closure is recommended in every case. Here we report a case of myiasis in a scalp wound caused by blunt force trauma to the area, in a male patient with a case history of alcohol and drug abuse. Seventy-one living larvae were extracted from the wound and determined as C. hominivorax in the Forensic Entomology Laboratory. Given the aggressiveness of these larvae, specific and quick diagnosis as well as the application of appropriate treatment is crucial.